2021
DOI: 10.3390/en14237830
|View full text |Cite
|
Sign up to set email alerts
|

Insurance Market Development, Energy Consumption, and Turkey’s CO2 Emissions. New Perspectives from a Bootstrap ARDL Test

Abstract: Many empirical studies have tested the linkage among CO2 emissions, economic growth, and consumption of energy; however, most have not tested the possible influence of insurance market development on their frameworks. This research aims to provide new perspectives on the empirical literature by exploring the role of insurance market development on environmental degradation. The study utilizes a new technique of the bootstrap Autoregressive Distributed Lag (ARDL) test as introduced by (McNown et al., 2018). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 32 publications
3
21
0
Order By: Relevance
“…In essence, the financial sector makes decisions about who to lend to and in what to invest. Therefore, their choices affect business practices and investment [6]. Some types of renewable energy, such as solar energy projects, are considered an expensive investment.…”
Section: Introductionmentioning
confidence: 99%
“…In essence, the financial sector makes decisions about who to lend to and in what to invest. Therefore, their choices affect business practices and investment [6]. Some types of renewable energy, such as solar energy projects, are considered an expensive investment.…”
Section: Introductionmentioning
confidence: 99%
“…The environmental changes trigger and lead to a shift in disease patterns ( 8 , 9 ). Over the past years, mortality and diseases have risen due to environmental pollution but also it is a hurdle in sustainable development ( 10 ). The Malaria outbreaks have befallen many temperate areas of the world.…”
Section: Introductionmentioning
confidence: 99%
“…[ 30 ] tested the linkage among financial sector development and consumption of renewable energy in India, over the period 1971–2015. Using the ordinary least squares test, the findings confirmed that there is positive link among financial development, and the level of renewable energy consumption in India [ 31 ]. Showed that there is a causal linkage between insurance sector development and Turkey’s renewable energy consumption.…”
Section: Review Of Literaturementioning
confidence: 89%
“…These steps will lead to overcoming the instability issue in the findings of traditional co-integration tests, as well as it will lead to provide a better result than other tests of co-integration. In this sense, the CV of ARDL bound test allows only for (one) tested variable to be endogenous, whereas in the updated ARDL test: the critical values allow for the endogeneity of selected explored variables [ 31 ]. Also, this technique is advisable for time-series that include more than (one) examined tested variable [ 45 ].…”
Section: Empirical Modelmentioning
confidence: 99%